Effect of different concentration of BAP on induction of polyembryony in jackfruit (Artocarpus heterophyllus Lam.) seeds - Ahmad Yusoff, Muhammad Al-Zubair (2017)
The jackfruit is one of the popular tropical fruits throughout the world. Its scienctific name is Artocarpus heterophyllus Lam. and it belongs to the Moraceae family. It is native to India and grows wild in the rain forests of Western Ghats of India. The jackfruit tree is eaten fresh as dissert. In Malaysia, the jackfruit is grown as a commercial commodity or grown as mixed commodity with few other fruit types such as durian, rambutan, duku and other fruits in traditional village. The jackfruit is usually propagated vegetatively using bud grafting technique. This technique requires the use of rootstock and selected scion materials. Currently the rootstock plants are raised from germinated seedlings where its seeds are collected from various clones throughout Malaysia. Due to its heterozygous behaviour, variation could be high among the seedlings and this can affect the performance of the scion when the jackfruit tree starts to bear fruits. Induction of polyembryony on jackfruit seeds can be an alternative approach in cloning and mass produce the jackfruit rootstock materials. This experiment is conducted to determine the best 6-Benzylaminopurine (BAP) treatment in inducing and increasing polyembryony on jackfruit’s seeds. Prior to germination, the seeds are soaked for two hours in various BAP treatments (0 mg/L, 10 mg/L, 15 mg/L, 20 mg/L, 25 mg/L and 30mg/ L) and then planted in trays containing sand. They are left for germination for eight weeks. The experiment is conducted using Randomized Complete Block Design (RCBD). It is observed that BAP treatments at 20 to 25 ml/L showed the highest percentage of polyembryony (62.5%) but the mean number of seedling induced per seed did not increased.